Criteria for Adjusting Supply and Demand Factors on the Regional Markets of Residential Real Estate (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article deals with the categories of supply and demand in the regional markets of residential real estate, the behavior of the buyer and seller on the market is determined by various factors, outlined the alternative strategies of construction companies on the basis of changing the subject proposal, it is proved that chaotic pricing occurs in the regional markets of residential real estate, which is not always subject to the laws of demand and supply, but the influence of non-price factors, factors of influence on demand on three types of real estate (residential, business her, warehouse).During the permanent changes of market structures and in accordance with the globalization challenges of the time, methodological and theoretical approaches to the place, role and significance of the market participant are also changed. Buyer and seller on the market being «alive» locomotives evolution of any location and type of market structure determine its viability. In addition, forming the subject of interaction and defining the vectors of the currentmarket situation are always in the center of research of the scientific community, which once increasing the relevance of scientific research. The economic actors of the market are buyers and sellers who enter into relations in relation to the sale and purchase of any product. Given the specifics of their interaction, each of the actors has a role and significance in the market. The buyer is in demand, at the same time the seller is the personification of the offer. Notonly stability and equilibrium in the local market, but also stability in the regional and national markets depends not only on the interaction and on the co-ordination between supply and demand.The current market system is represented by a set of diverse markets that represent a huge number of goods and services. Despite all the special attention should be paid to the real estate market, which, given the significant share in the gross national product and gross regional product, high level of budget revenues, capitalization opportunities through lease of its facilities, institutional branching and scale of sales operations are important. the economy sector.
Keywords: regional real estate, developers, coefficient of elasticity of demand, elasticity of the offer, primary real estatemarket, secondary real estate market.